Identification of Acinetobacter baumannii from clinical ACB complex isolates of nine sentinel surveillance sites of IEDCR: focus on their distribution and antibiotic susceptibility pattern - Islam, Tarikul; Hossen, Md. Abir (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Microbiology, 2024.